The Indonesia Corporate Governance Manual - International Finance Corporation (International Finance Corporation, Jakarta, 2017)
International Finance Corporation (IFC), a member of the World Bank Group, creates opportunity for people to escape poverty and improve their lives. The Indonesia Corporate Governance Manual (CG Manual) was commissioned by IFC as part of the Indonesia Corporate Governance Program that IFC is implementing in Indonesia since 2012. As part of this Program, IFC has established a formal cooperation with Otoritas Jasa Keuangan (OJK). A key product of this cooperation between IFC and OJK is the development of this Indonesia Corporate Governance Manual, which serves as a learning instrument to benchmark existing standards and practices in Indonesia with internationally recognized best practices. In this respect, this Corporate Governance Manual should be considered as a major tool for Corporate Governance in Indonesia as it targets a wide spectrum of stakeholders, such as directors and commissioners, academics, policymakers, corporate governance experts and more generally, individuals and institutions interested to know about the corporate governance framework in Indonesia. IFC is happy to be part of this initiative with OJK and remains committed to helping raise governance standards across the market and contribute to a sustainable private sector in Indonesia. The Fifteen chapters of the Manual focus on the key corporate governance issues. All issues are closely examined through Indonesian law and regulations and when applicable, internationally recognized best practices. While it is recommended to read the entire Manual to gain a full understanding of the corporate governance framework in Indonesia, it is not necessary to read all the chapters in chronological order. The reader is encouraged to begin with a topic of interest and follow the links and references included in the text for guidance to other chapters. Examples, illustrations, and checklists are included to make the Manual clear and useful.